EFFECTIVENESS OF GUIDED DISCOVERY-BASED MODULE: A CASE STUDY IN PADANG CITY, INDONESIA - Delsi Kariman; Yulyanti Harisman; Anny Sovia; Rully Charitas Indra Prahmana (Journal on Mathematics Education, 2019)
One of the research objectives was formulated to improve the quality of education, namely by understanding the problems of students and teachers. There were three main groups of quality characteristics of education highlighted in scientific and academic literature in Russia, namely the quality of educational objectives, the quality of the educational process, and the quality of educational outcomes. The problem of education in Indonesia is the quality of the education process. The development of teaching materials is an alternative to improve the quality of the education process. Research so far has only focused on the implementation of learning models by teachers in the classroom, but the model is not integrated into the teaching materials used. This paper examines how the effectiveness of a product that has been developed for two years on 27 Indonesian students. The product produced is a guided discovery-based module in the Complex Analysis subject. This product was developed after the preliminary analysis (defining) process. Students are given 16 modules during lectures; then students are given a final test containing all the competencies that must be achieved. Test results are scored, and statistical analyses are conducted to compare them with student score before using the module. The test used is t-test. The design used is one of the experimental research designs, One Shot Case Study. The results of the study showed that students who were taught with modules developed effectively to improve student learning outcomes. Further research can be done by implementing different learning models in teaching materials.